2006
DOI: 10.2174/156800906777723949
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotide Reductase Inhibitors and Future Drug Design

Abstract: Ribonucleotide reductase (RR) is a multisubunit enzyme responsible for the reduction of ribonucleotides to their corresponding deoxyribonucleotides, which are building blocks for DNA replication and repair. The key role of RR in DNA synthesis and cell growth control has made it an important target for anticancer therapy. Increased RR activity has been associated with malignant transformation and tumor cell growth. Efforts for new RR inhibitors have been made in basic and translational research. In recent years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
253
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(257 citation statements)
references
References 266 publications
(250 reference statements)
1
253
1
2
Order By: Relevance
“…Our data support the hypothesis that FBH1 controls a mechanism to eliminate cells via apoptosis under conditions of elevated replication stress (and oncogene activation) when too many forks have collapsed and restart efforts can be harmful in allowing the propagation of cells with genomic instability. Our results also have clinical relevance in providing insight into the response to genotoxic stress caused by HU, a chemotherapeutic drug used in the treatment of a number of malignancies, as well as polycythemia vera and sickle cell anemia 24,25 . Indeed, several DNA replication inhibitors, including gemcitabine, 6-thioguanine and Fludarabine phosphate, are used for the treatment of a number of a wide range of cancers 24 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our data support the hypothesis that FBH1 controls a mechanism to eliminate cells via apoptosis under conditions of elevated replication stress (and oncogene activation) when too many forks have collapsed and restart efforts can be harmful in allowing the propagation of cells with genomic instability. Our results also have clinical relevance in providing insight into the response to genotoxic stress caused by HU, a chemotherapeutic drug used in the treatment of a number of malignancies, as well as polycythemia vera and sickle cell anemia 24,25 . Indeed, several DNA replication inhibitors, including gemcitabine, 6-thioguanine and Fludarabine phosphate, are used for the treatment of a number of a wide range of cancers 24 .…”
Section: Discussionmentioning
confidence: 73%
“…Our results also have clinical relevance in providing insight into the response to genotoxic stress caused by HU, a chemotherapeutic drug used in the treatment of a number of malignancies, as well as polycythemia vera and sickle cell anemia 24,25 . Indeed, several DNA replication inhibitors, including gemcitabine, 6-thioguanine and Fludarabine phosphate, are used for the treatment of a number of a wide range of cancers 24 . Finally, our findings suggest that the assessment of FBH1 functional status might potentially be used to identify patients that would benefit from treatment with HU or other drugs with a similar mechanism of action.…”
Section: Discussionmentioning
confidence: 73%
“…A number of anti-cancer drugs function to inhibit RNR activity, including hydroxyurea (HU), gemcitabine 59-diphosphate, 3-aminopyridine-2-carboxaldehyde thiosemicarbazone (3AP), [Tris(1,10-phenanthroline)-lanthanum(III)] trithiocyanate (KP772), motexafin gadolinium (MGd), triapine, and others (for review, see Shao et al 2006). Our findings indicate that these drugs are likely to not only inhibit DNA replication, but are expected also to block efficient HR, and therefore sensitize cells to the types of DNA damage and damaging agents that require HR repair.…”
Section: Regulation Of Rnr and Efficient Hrmentioning
confidence: 99%
“…The higher demand for iron may at least partly be explained by the increased activity of iron dependent enzymes such as ribonucleotide reductase (RR), a rate-limiting step in DNA synthesis [34]. Indeed it has also been demonstrated that the activity and expression of RR is increased in tumor cells indicating a high level DNA synthesis in these cells [35].…”
Section: Page 13 Of 30mentioning
confidence: 99%